Eksistensi Instrumen Hukum Lokal dalam menjamin hak-hak masyarakat adat dalam perspektif informal Justice System di Kep Kei Besar - Gilbert Marc Baljanan; Lucia Charlota Octovina Tahamata; Saartje Sarah Alfons (SANISA: Jurnal Kreativitas Mahasiswa Hukum, 2022)
Introduction: Society is a group of people who are closely intertwined because of certain systems, certain traditions, and certain laws that are the same, and lead to the collective life of people with certain systems and certain traditions in Indonesia. it is a living alliance that is still original growing as a legal order that is cared for by its customary leaders: In a case settlement and law enforcement cannot be done only in a formal way but can also be done through informal channels. This informal path or commonly referred to as the informal justice system in which problems that occur in indigenous peoples are resolved according to custom and applicable rules where the informal case resolution process is carried out by prior examination by community officials and traditional leaders.Purposes of the Research:  To examine and find out the existence of local legal instruments in guaranteeing the rights of indigenous peoples in the perspective of the informal justice system in the Kei Besar Islands.Methods of the Research: The method used in writing this paper is literature study and observation. The main types of references used in the study of literature are books, journals and scientific articles. The data is used as a basis for analyzing and explaining the problem in a discussion. The analysis technique is descriptive argumentative. Meanwhile, observations and interviews were conducted with civil law lawyers at Pattimura University.Results of the Research: Local Legal Instruments located in Kep. Kei Besar, in order to create an acknowledgment, must be written and its credibility recognized by positive laws regulated in Indonesia. In addition, the Informal Justice System has proven to be effectively able to answer various kinds of customary issues, such as in Pakraman Village, Bali. Our local legal instruments must also contain procedures for resolving disputes by a customary court. It is important that the Indigenous Law Community Bill must be ratified immediately in order to acknowledge and create credibility rather than the existence of the Indigenous Law Community itself